Effect of the Song "Diri" by Tulus on Self-Affirmation Among University Students: An Experimental Study - Nurul Wardhani; Davina Rizkika Tamawulan; Ajeng Rachmah Purnama Sari; Nevya Alya Mardhiyah; Risya Khairunnisa Nuraini; Najmi Cahyani Safitri; Daffaʼ Mulya Rahman Sulistya (Kajian Psikologi dan Kesehatan Mental, 2025)
Purpose: University students are highly vulnerable to psychological distress. Self-affirmation, defined as reflecting on core personal values to maintain self-integrity under threat, may serve as a protective mechanism. This study examines the effect of listening to the Indonesian song “Diri” by Tulus on self-affirmation among psychology students at Universitas Padjadjaran (UNPAD). Methodology: A true experimental pretest posttest design was used with 78 psychology students (cohorts 2022–2023) selected via stratified random sampling using UNPAD SAS. Selfaffirmation was measured using the SSAM. The song was delivered via Spotify through Zoom. Normality was tested using Kolmogorov–Smirnov; due to non-normal data, the Wilcoxon Signed Rank Test was applied in SPSS 22. Effect size was calculated using r = |Z|/?N.Results: Mean SSAM scores increased from 5.14 (SD = 0.73) to 5.54 (SD = 0.75), a 7.8% improvement. The Wilcoxon test showed a significant difference (Z = ?6.355, p < .001) with a large effect size (r = 0.719).Conclusion: Listening to “Diri” significantly enhances selfaffirmation, indicating that music with affirming lyrical content may function as an accessible psychological intervention. Limitations: The study lacks a control group, uses a single university sample, and has limited ecological validity due to online administration.Contribution: This is the first experimental evidence that an Indonesian popular song can function as a self-affirmation stimulus, contributing to music psychology and low cost mental health interventions in higher education.